APLIKASI PROMOSI PROPERTI BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Gunawan, Heri; Maslan, Andi (LPPM Universitas Putera Batam, 2022)
Until now, technological advances that continue to develop rapidly have made all jobs in life switch to using complex of technology that can facilitate all types of business activities will be easier, faster, and more efficient PT Winner Nusantara Jaya is a company engaged in property sales. The problem often faced by property sales companies is that they still use print media and social media in property promotion so it is necessary to have an information system that contains complete information about the properties that exist in PT. winner archipelago jaya information on business marketing activities as well as sales. In modeling the system that will be used by researchers is UML for the research program using the PHP programming language and also for the researcher database using MYSQL the result of the design of this information system is to assist consumers in finding property products at PT. winner archipelago jaya.